Fish oil diet may reduce inflammatory levels in the liver of middle-aged rats - Li, Yingqiu (Sci Rep, 2017)
The impact of dietary soybean oil, lard and fish oil on physiological responses in middle age is little studied. In this study, we investigated the changes of oxidative stress, inflammatory cytokines, telomere length, and age-related gene expression in the liver of middle-aged rats in response to the above three fat diets. Male Sprague Dawley rats (12 months old) were fed AIN-93M diets for 3 months, in which soybean oil was equivalently replaced by lard or fish oil. As compared to the lard diet, intake of fish oil diet significantly decreased body weight gain, white blood cell count, and levels of hepatic triacylglycerol, total cholesterol, fat accumulation, low-density lipoprotein, oxidative stress and inflammatory cytokines (P < 0.05), but increased telomere length (P < 0.05). On the other hand, lard diet and soybean oil diet showed great similarity in the above variables. PCR array analysis further indicated that fish oil diet significantly down-regulated gene expression related to inflammatory response, apoptosis, DNA binding, proteostasis and telomere attrition. Differentially expressed genes were enriched in the complement and coagulation cascades pathways. Such physiological and molecular responses could be due to different fatty acid composition in fish oil, lard and soybean oil.